Neuroimaging Offers Low Yield in Children Positive for SARS-CoV-2 - Orman, G.; Desai, N.K.; Kralik, S.F.; Meoded, A.; Seghers, V.J.; Annapragada, A.V.; Huisman, T.A.G.M. (American Journal of Neuroradiology, 2021)
SUMMARY: The coronavirus disease 2019 (COVID-19) pandemic caused by Severe Acute Respiratory Syndrome coronavirus disease 2 (SARS CoV-2) most commonly presents with respiratory disease, but neurologic complications are being reported. We aimed to investigate the rate of positive neuroimaging findings in children positive for SARS-CoV-2 referred for neuroimaging between March 18 and September 30, 2020. We found that 10% (n = 2) had acute findings. Our results may suggest that in children, neurologic involvement in COVID-19 is rare, neuroimaging has a low yield in diagnosis, and acute neuroimaging should involve careful risk-benefit analysis.COVID-19coronavirus disease 2019MIS-Cmultisystem inflammatory syndrome in childrenSARS-CoV-2Severe Acute Respiratory Syndrome coronavirus disease 2